THE EFFECT OF LEARNING MODEL CONCEPTUAL CHANGE BASED INSTRUCTION (CCBI) AND GENERATIVE LEARNING MODEL (GLM) AND CRITICAL THINKING SKILLS TO THE LEARNING OUTCOMES OF ACID-BASE - Wiwik Setiawan; Suwirman Nuryadin; Maria Paristiowati (Lembaga Penelitian UM Metro, 2016)
The purpose of this study was to determine effect of learning model Conceptual Change Based Instruction (CCBI) and Generative Learning Model (GLM) and critical thinking skills to the learning outcomes of acid-base.The research was conducted in SMA Bakti Mulya 400 lesson year 2015-2016. In this study were randomly selected sample (cluster random sampling). Data of learning outcomes and critical thinking skills are collected in the form of multiple-choice written test type. Data were analyzed using descriptive statistics and two ways ANOVA. Based on research, it was found. First there is a difference in student learning outcomes significantly between models CCBI with GLM model (F = 4.288, p <0.05), the second there is a difference in student learning outcomes significantly in the group of students with high critical thinking skills among models CCBI with GLM model (F = 4.34, p<0.05), the third there was no difference in student learning outcomes significantly in the group of students who have the ability to think critically low between models CCBI with GLM model (F = 0.194, p<0.05), and the fourth there are significant interaction between the learning model with the ability to think critically (F = 5.122, p<0.05).